Coumarin-Chalcone derivatives as promising antioxidant agents targeting ischemia/reperfusion injury through Nrf2 pathway activation - Mohammadnia, Maryam; Emamgholipour, Zahra; Peytam, Fariba; Nikbakhtzadeh, Marjan; Hosseindoost, Saereh; Alsaeed, Salwa Basheer; Foroumadi, Alireza (Academic Press Inc Elsevier Science, 2025)
Ischemic stroke remains a major global cause of mortality. Reperfusion therapy with thrombolysis paradoxically raises reactive oxygen species (ROS) and causes cerebral ischemia-reperfusion injury (CIRI). To address this challenge, antioxidants, which directly neutralize ROS or indirectly activate the KEAP1/Nrf2/ARE pathway, have emerged as promising strategies. Given the antioxidant properties of natural coumarins and chalcones, we designed and synthesized coumarin-chalcone analogs to assess their neuroprotective potential against CIRI by activating the Nrf2 pathway. Interestingly, the in vitro H2O2-induced oxidative stress model demonstrated that compounds 7f, 7j, and 7l significantly enhanced the viability of hippocampal neuronal cells following H2O2 exposure. Further in vivo evaluation of 7l using the 2VO cerebral hypoperfusion model demonstrated improvements in motor function, sensory response, memory, and hippocampal neuronal preservation. Furthermore, molecular docking and molecular dynamics simulations confirmed the stable binding of 7l compound in the Keap1 Kelch domain. It warrants its ability to disrupt Keap1-Nrf2 interactions and activate antioxidant defense mechanisms. This was confirmed biochemically by increased expression of Nrf2, SOD, and CAT, along with reduced malondialdehyde levels in the treated group. Overall, these results highlight compound 7l as a promising neuroprotective candidate for combating CIRI through antioxidant and Nrf2-mediated mechanisms.
Keywords: Antioxidant; Coumarin-chalcone derivatives; Ischemia/reperfusion injury; Keap1; Neuroprotective; Nrf2